2019
DOI: 10.1186/s12884-019-2588-9
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors and their individual contributions to caesarean delivery among married women in Bangladesh: analysis of Bangladesh demographic and health survey data

Abstract: BackgroundCaesarean section (CS) delivery has a significant effect on maternal and neonatal health especially in a developing country like Bangladesh. The aim of the study was to determine the risk factors and their individual contribution to CS delivery among Bangladeshi married women in reproductive age.MethodsThe cross sectional secondary data was used in this study. Data was extracted from Bangladesh Demographic and Health Survey (BDHS), 2014 dataset. BDHS-2014 collected data from all over Bangladesh. Step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 22 publications
10
68
0
Order By: Relevance
“…Mothers from higher-income family usually live with more comforts and facilities, and therefore, might be more anxious about the labor pain of vaginal delivery and might go under CS delivery. This outcome might be regarded as consistent and replicable to the previous findings [8,9,26]. A study explicated that the CS delivery rate was increasing with the upward of average income in both urban and rural areas in Bangladesh, and the rate was higher in the urban area compared to the rural area [26].…”
Section: Plos Onesupporting
confidence: 80%
See 1 more Smart Citation
“…Mothers from higher-income family usually live with more comforts and facilities, and therefore, might be more anxious about the labor pain of vaginal delivery and might go under CS delivery. This outcome might be regarded as consistent and replicable to the previous findings [8,9,26]. A study explicated that the CS delivery rate was increasing with the upward of average income in both urban and rural areas in Bangladesh, and the rate was higher in the urban area compared to the rural area [26].…”
Section: Plos Onesupporting
confidence: 80%
“…Recently in Bangladesh, it is noticeable some mothers go under CS delivery without any complications. Several studies conducted in Bangladesh have identified a number of socioeconomic and demographic factors associated with CS delivery, such as mothers' education, place of residence, wealth index, mothers' age, age at marriage, age at first birth, parity, birth order, antenatal visit, husband occupation, delivery in the private sector, religion, geographical region [8][9][10][11][12]. Also, some other studies available in the literature for several countries identified various socio-economic, demographic, physical facilities, and community interrelated factors significantly associated with making decisions to undergo institutional delivery [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There was sharp rise between 2017 and 2018.Sub division of emergency and elective caesarean sections in 2017 indicates that elective caesareans were 81.7 % and emergency caesarean sections were 18.3 %. Comparison of caesarean section with our neighbouring countries like Bangladesh, shows an increase in last 10years [18]. Worldwide, last decade has shown a rapid rise in delivery via caesarean section more than 20% in both developed and under developed nations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the risk of disease was higher in the Khulna division in the MICS surveys. Most of the women in these areas are educated and they belong to middle-class and rich families and have access to and ability to undergo C-section delivery [ 28 ]. Nowadays, educated pregnant women want to avoid vaginal delivery in fear of labor pain and other conveniences.…”
Section: Discussionmentioning
confidence: 99%